Blaschkoid lichen planus in an adult Kashmiri male: a rare presentation - Parvaiz Anwar Rather; Iffat Hassan (Our Dermatology Online, 2013)
Lichen planus (LP) is common acquired dermatoses with several morphological forms. Linear lichen planus is frequently seen but cases of zonal/ zosteriform/ dermatomal/ blaschkoid LP are rare. We report a case of blaschkoid LP along with scalp LP in a 42 year old adult Kashmiri male. We report the case to add one more case to the list of this rare form of LP, with the peculiarity in our case of late onset of presentation and coexisting scalp LP, and review the literature to address to the confusion about the various related terms.